CPB 2. Are Large Panicle-Type Rice Genotypes Suitable for Wet Season Planting? (The Philippine Journal of Crop Science, 2018)
Large panicle is not always associated with high yield in the wet season (WS). Genotypes with large panicles are usually taller and have longer growth duration, often resulting in poor grain filling. However, genotypes with a large panicle size (spikelets per panicle) with no increase in plant height (Pan/Ht) and high harvest index (HI) with no decrease in plant height (HI*Ht) may be selected for WS conditions. Field experiments were conducted in the 2012 WS at the IRRI farm, Los Baños, Laguna and 2013 DS at PhilRice, Muñoz, Nueva Ecija, to identify rice genotypes for suitability in the WS using the abovementioned selection criteria. Each experiment had a split-plot randomized complete block design with planting density (D1=25 hills m-2) as main plot and genotype (12) as subplot with four replications. Averaged across genotype and density, grain yield was 6.41 t ha-1 in the WS and 8.49 t ha-1 in the DS. Correlation between grain yield and panicle size was positive and significant in the WS (r=0.346*) but not in the DS (r=-0.141ns ). Panicle size was positively correlated with plant height at flowering in the DS (r=0.682*) , but it was negative and not significant in the WS (r=0.196ns). Averaged across genotypes, plants at D1 had significantly larger Pan/Ht than D2 in both the WS (25%) and DS (22%). Intra-density genotypic differences were observed in the WS but not in the DS, which indicates the importance of planting density in the WS. Across genotypes, significantly higher HI*Ht was observed in D1 than in D2 in both the WS (15.8%) and DS (9.1%). Genotypic differences in HI*Ht within density were observed in both seasons. Genotypes with larger panicle size with no increase and high HI with no decrease in height may be suitable for WS planting.